1991
DOI: 10.1111/j.1472-765x.1991.tb00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in ciliate protozoa in the rumen of black buck (Antilope cervicapra) fed green forage

Abstract: The protozoa in the rumen of a black buck were a B‐type population with numbers varying between 0·31 and 0·61 times 106cells/ml rumen liquor, when the animal was fed either vegetative green oat or third cut berseem. The total protozoa, total holotrichs, Dasytricha, total spirotrichs and small spirotrichs were significantly higher (P < 0·01) on berseem feeding than those on oat feeding, while the numbers of Isotricha and large spirotrichs were unaffected by change of diet. Numerically the most important group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 11 publications
3
52
0
Order By: Relevance
“…The passage rate of feed is faster and thus fibre degradation is lower. Kempton et al (1976) reported 48% and 36% crude fibre digestibility i n sheep a n d grey kangaroo, respectively.…”
Section: Non-ruminant Herbivoresmentioning
confidence: 98%
See 1 more Smart Citation
“…The passage rate of feed is faster and thus fibre degradation is lower. Kempton et al (1976) reported 48% and 36% crude fibre digestibility i n sheep a n d grey kangaroo, respectively.…”
Section: Non-ruminant Herbivoresmentioning
confidence: 98%
“…Numerically the most important group of protozoa i.e. small spirotrichs (74-75% of total numbers) accounted for only 10-14% of total protozoal mass, while holotrichs were 14-17% of total numbers, but contributed 41-42% of total protozoal mass ( Table 2, Kamra et al, 1991). The number of total protozoal mass and spirotrichs increased significantly on inclusion of maize grain in the diet of blackbuck (Agarwal et al, 1996).…”
Section: Ruminant Animalsmentioning
confidence: 99%
“…Rumen fluid samples were collected from intact animal using stomach tube at 0, 4, 8, 12, 18 and 24 h post feeding for pH determination, analysis of total volatile fatty acids (TVFA by Barnett and Reid, 1957) and ammonia nitrogen (NH 3 -N by Conway, 1962) and enumeration of ciliate protozoa population (Kamra et al, 1991). Rumen contents (40 to 50 ml) were sampled and pH measured within 5 min of aspiration.…”
Section: Nutrient Utilisation and Rumen Fermentationmentioning
confidence: 99%
“…Ruminal fluid was kept in pre-warmed thermos containers (39 ºC) and transport to the laboratory and analyzed immediately for pH. From these samples, 2ml of rumen fluid was collected in a tube containing 4 ml of methyl greenformalin saline solution (MFS) for protozoa counts as per the procedure of Kamra et al (1991). NH3-N concentration was measured by using micro-kjeldahl steam distillation according to .…”
Section: Rumen Fluid Analysismentioning
confidence: 99%
“…An aliquota of 3 mL of liquid was collected for NH3-N concentration, measured according to and ruminal protozoa counts were microscopically counted according to the procedure described by Kamra et al (1991). Short chain fatty acids (SCFA) was determined according to .…”
Section: In Vitro Ruminal Parametersmentioning
confidence: 99%